PENGARUH KUALITAS LABA TERHADAP NILAI PERUSAHAAN DENGAN REAKSI PASAR SEBAGAI VARIABEL INTERVENING - Jonathan, Jonathan; Machdar, Nera Marinda (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to determine the effect of earnings quality to firm value with market reaction as intervening variable. This study conducted by using the secondary data. Analysis method was the multiple linear regression analysis by utilizing SPSS 22 program and path analysis. The population in this study is the manufacturing companies listed on the Indonesian Stock Exchange during the period 2010-2015. The determination of the sample used a purposive sampling method and obtained 104 companies as a sample. The result showed that (a) earnings quality significantly negative affect on firm value, (b) earnings quality doesn’t effect significantly of firm value through market reaction, (c) earnings quality doesn’t effect significantly of market reaction and (d) debt equity ration and leverage as control variable, only debt quity ratio significantly effect of firm value . Keywords: earning quality, firm value, market reaction, abnormal return